Prevalence of Unfavorable Video-Urodynamic Findings and Clinical Implications in Patients with Minimally Conscious State/Unresponsive Wakefulness Syndrome: A Retrospective Descriptive Analysis - Francois Leboutte; Christian Engesser; Leutrim Zahiti; Cyrill A. Rentsch; Helge Seifert; Ralf Anding; Margret Hund-Georgiadis; Sandra Möhr; Matthias Walter (Biomedicines, 2023)
The aim of this retrospective exploratory study was to investigate the prevalence of unfavorable findings during video-urodynamic studies (VUDS) in patients with minimally conscious state (MCS)/unresponsive wakefulness syndrome (UWS) and whether management of the lower urinary tract (LUT) was adjusted accordingly. A retrospective chart review was conducted to screen for patients diagnosed with MCS/UWS at our rehabilitation center between 2011 and 2020. Patients 18 years or older were included and underwent baseline VUDS after being diagnosed with MCS/UWS. We analyzed urodynamic parameters and subsequent changes in LUT management in this cohort. In total, 32 patients (7 females, 25 males, median age 37 years) with MCS/UWS were included for analysis. While at least one unfavorable VUDS finding (i.e., neurogenic detrusor overactivity [NDO], detrusor sphincter dyssynergia {DSD, high maximum detrusor pressure during storage phase [>40 cmH2O], low-compliance bladder [<20 mL/cmH2O], and vesico–uretero–renal reflux [VUR]) was found in each patient, NDO (78.1%, 25/32) and DSD (68.8%, 22/32) were the two most frequent unfavorable VUDS findings. Following baseline VUDS, new LUT treatment options were established in 56.3% (18/32) of all patients. In addition, bladder-emptying methods were changed in 46.9% (15/32) of all patients, resulting in fewer patients relying on indwelling catheters. Our retrospective exploratory study revealed a high prevalence of NDO and DSD in patients with MCS/UWS, illustrating the importance of VUDS to adapt LUT management in this cohort accordingly.